(untitled) (Modern Information Technologies and Innovation Methodologies of Education in Professional Training Methodology Theory Experience Problems, 2022)
The article presents a way of organizing lesson on medical informatics on the topic “Individualmedical charts...” for medical students of the Faculty of Dentistry. The authors cite examples of professionally orientedtasks that have an integrative connection with future medical activities and clinical disciplines that are being studied byfuture dentists in parallel with medical informatics. Interrelated in content theoretical and practical tasks were selectedto study the topic, that made it possible for implementation of a logical reasonable transition from theory to practiceand acquisition professional skills based on the knowledge gained. In particular, the theoretical tasks involvefamiliarizing future dentists with the state legislative requirements for structure of medical chart of a dental patientand rules its filling out. The practical tasks for creating dental histories of patients are considered on the example ofstudents' work in the program MS Access and also it is mentioned about the possibility of using these data to study thework principle of already developed electronic medical records. Creating an electronic database of medical charts inthe program MS Access involves students' work with tables, queries, forms, reports, moreover students applyingdifferent options for their filling out and creation, that increases the level of information and communicationcompetence of future dentists.